'Manhattan weighed on his eyelid' : reading Ted Hughes in the context of four American writers - Groszewski, Gillian M. (Trinity College (Dublin, Ireland). School of English, 2012)
The introduction to this thesis documents and establishes Ted Hughes' growing interest in American writing while at Cambridge and suggests that Hughes' engagement with American writing from this point in his career onwards was extremely beneficial and inspirational. The introduction also considers why it is that Hughes' work has almost exclusively been read in the context of his engagement with other British writers. At the outset, the phenomenon of what Kate Clanchy has called 'the nationalisation of Ted Hughes' is explored. Hughes' early recognition and positive reviews in the US are also read in the context of two opposing groupings of poetry in Britain in the 1950s - the Movement and 'The New Poetry'. Hughes' identification with American poetics and his relocation to the US at the height of the Movement are considered as having been crucial to his early success.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin.